Pengaruh iklim organisasi terhadap organizational citizenship behavior pada karyawan - Cahyani, Anindya; Winarsunu, Tulus; Nur Rokhmah , Sakinah (Universitas Muhammadiyah Malang, 2024)
The organizational climate in a company plays an important role in the formation and improvement of OCB in employees. Having OCB in employees will benefit the organization or company. For companies, OCB can function to help new employees adapt to their positions as quickly as possible, and help teams to solve complex problems. For employees, this can increase their sense of self-efficacy, personal reputation, and job satisfaction. The purpose of this research is to determine and prove the influence of organizational climate on OCB in employees. This research uses a non-experimental quantitative approach, with a correlational research design. This study used a probability sampling technique with simple random with a total of 236 respondents. The research instruments used were the Organizational Citizenship Behavior Scale and The Organizational Climate Questionnaire (OCQ). Data analysis uses simple linear regression analysis. The research results show a positive influence between organizational climate on Organizational Citizenship Behavior. This means that the higher the organizational climate experienced by employees, the higher the OCB displayed by employees.